EVALUASI KINERJA PENCAHAYAAN ALAMI DAN KENYAMANAN VISUAL RUANG KELAS GEDUNG A VOKASI UNDIP - Riana Arum Kusuma; Agung Budi Surdjono (Universitas Katolik Soegijapranata, 2026)
The implementation of green building concepts in tropical climates often creates a paradox between energy efficiency and visual comfort. Building A of the Vocational School of UNDIP holds EDGE Advanced certification from the Green Building Council Indonesia (2021), recognizing 65% energy savings through facade strategies and daylighting optimization. This study aims to: (1) evaluate illuminance distribution across 8 classrooms (A1.1, A2.3, A3.1–A3.4, A4.3–A4.4) against SNI 03-6197-2000; (2) analyze glare potential using the Daylight Glare Probability (DGP) indicator; (3) identify user perceptions and adaptive behaviors; and (4) formulate facade design recommendations based on vertical zoning. Using a quantitative Post-Occupancy Evaluation approach, the study integrates Climate-Based Daylight Modeling simulation via Velux Daylight Visualizer at 09:00, 12:00, and 16:00 on June 21, September 21, and December 21 with questionnaires administered to 64 student respondents. Findings empirically confirm the green building paradox: despite average illuminance meeting SNI thresholds, extreme distribution disparities and critical DGP values in west-facing classrooms at 16:00 indicate severe glare. User visual stress perceptions and negative adaptive behaviors align with simulation results, confirming the failure of existing vertical shading to redistribute daylight. Light shelves and extended overhangs based on vertical zoning are recommended to restore a human-centric learning environment.